2019
DOI: 10.1123/jab.2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Validating Virtual Time to Contact With Home-Based Technology in Young and Older Adults

Abstract: Virtual time to contact (VTC) is a measure of postural stability that estimates the virtual time it would take to reach an individual's stability boundary. This study aimed to validate VTC as measured by a depth sensor, and to determine if VTC from the depth sensor distinguishes between older adult fallers and non-fallers compared to a force platform. VTC was assessed in 10 young and 20 older adults by having participants lean in a circular direction followed by five balance tests: eyes open, dual task, eyes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…This result suggests that, for naturally occurring instabilities, the spatial and temporal proximity of the center of pressure to the stability boundary is the most crucial variable triggering the cortical sign of postural instability. In contrast to previous studies that obtained similar findings [13,18,33,39,51,52], our findings resulted from a direct comparison of the prediction ability of four biomechanical parameters during a single epoch. While we showed the utility of this approach in the context of a standing balance task, it can be extended to other dynamic situations like walking.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This result suggests that, for naturally occurring instabilities, the spatial and temporal proximity of the center of pressure to the stability boundary is the most crucial variable triggering the cortical sign of postural instability. In contrast to previous studies that obtained similar findings [13,18,33,39,51,52], our findings resulted from a direct comparison of the prediction ability of four biomechanical parameters during a single epoch. While we showed the utility of this approach in the context of a standing balance task, it can be extended to other dynamic situations like walking.…”
Section: Discussioncontrasting
confidence: 80%
“…Slobounov et al were first to propose that TTB could be the neural detector of postural instability [13,33], as it combines both spatial and temporal dynamics of postural sway. Various studies over the years, including those from our laboratory, have shown the effectiveness of TTB as a valid measure of postural stability in various populations or scenarios, including older adults [51,52], people with multiple sclerosis [59,60], ankle instability [61], Parkinson's disease [62], virtual temporary lesion [15], as well as in astronauts [39] and single vs. dual-task differences [16,18]. Postural stability measured by TTB has also been linked to greater fall risk [52,60,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation